2013
DOI: 10.1111/jre.12094
|View full text |Cite
|
Sign up to set email alerts
|

Root caries: a periodontal perspective

Abstract: Research regarding root caries in age-specific (elderly) periodontal patients is needed. Improved oral hygiene practices, locally applied preventive measures, good dietary habits and regular dental check-ups are crucial approaches to prevent both periodontal disease progression and root caries. Periodontal patients with root exposure should follow a strict root caries prevention protocol, as an integral component of their periodontal maintenance therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 200 publications
(272 reference statements)
5
60
0
6
Order By: Relevance
“…As cited by Shen et al and Bignozzi et al, they reported scanning electron microscopy observations revealed various patterns of bacterial coaggregation in RC lesions. Especially in cases of gingival recession, the root surface becomes more exposed, increasing the likelihood of developing RC . Synergistic growth was observed in cocultures of L. acidophilus with S. mutans and A. israeli as well as L. acidophilus , producing greater acidogenic and cariogenic effects on the root surface.…”
Section: Historical Development Of Caries From Bacteriamentioning
confidence: 76%
“…As cited by Shen et al and Bignozzi et al, they reported scanning electron microscopy observations revealed various patterns of bacterial coaggregation in RC lesions. Especially in cases of gingival recession, the root surface becomes more exposed, increasing the likelihood of developing RC . Synergistic growth was observed in cocultures of L. acidophilus with S. mutans and A. israeli as well as L. acidophilus , producing greater acidogenic and cariogenic effects on the root surface.…”
Section: Historical Development Of Caries From Bacteriamentioning
confidence: 76%
“…When root surfaces are exposed to the oral cavity, caries can initiate and progress more rapidly on root surfaces than on enamel surfaces [Ogaard et al, 1988;Keltjens et al, 1993;Kidd and Fejerskov, 2004;Bignozzi et al, 2014;Wierichs and Meyer-Lueckel, 2015]. Root surface caries is a biochemical process initiated by the demineralization, which in turn exposes the organic materials to degradation [Nyvad and Fejerskov, 1990;Kleter et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…Both enamel and dentin/root caries are mainly initiated by the demineralization of the tooth surface through bacterial acid production from sugar [Deng and ten Cate, 2004;Kidd and Fejerskov, 2004;Selwitz et al, 2007;Featherstone, 2008;González-Cabezas, 2010;Bignozzi et al, 2014]. Therefore, it is necessary to evaluate tooth solubility at the tooth/bacteria interface, where the pH is gradually decreased by bacterial sugar metabolism and the solubility of the tooth surface can be modified by changes in pH and/or mineral concentration at the interface.…”
Section: © 2017 S Karger Ag Baselmentioning
confidence: 99%
“…In such a patient, there may be a “food trap” (build-up of food particles and dense plaque between teeth) adjacent to a wide and tight interproximal contact—in addition to some gingival recession between these teeth. If ignored over time, interproximal tooth decay could easily develop in this area which could even lead to tooth loss 8 . Ideally, a person would both floss and use an appropriately-sized proxy brush in this area.…”
Section: Introductionmentioning
confidence: 99%